Non-invasive Imaging in the Evaluation of Cardiac Shunts for Interventional Closure - Pushparajah, Kuberan (Frontiers in Cardiovascular Medicine, 2021)
Multimodality imaging provides important information to guide patient selection and pre-procedural decision making for shunt lesions in CHD. While echocardiography, CT and CMR are well established, 3D printing and now virtual reality imaging are beginning to show promise.